Design of a Flexible Pavement for Kabwohe- Masherukabuhweju Gravel Road Using Road Note and CBR. - Twinamatsiko, Zilberbel (Kabale University, 2023)
This report consists of proposed design of a flexible pavement for Kabwohe-Masheruka-Buhweju gravel road t which stretches a distance of 1km. The project design was started after field studies showed that travel time was greatly reduced, inadequate cross section high maintenance costs which were reflected on the existing road. To design, assessment of the physical properties of the subgrade was carried out, existing traffic was obtained by manual counts to give ADT on the road, Consistence of subgrade strength was done through field and lab tests. From the results obtained, traffic range was established, the Average Daily Traffic was 490Vehicles/day excluding non- motorised traffic and Motorcycles taking up the greatest percentage of traffic , the sub grade physical properties such specific gravity and sieve analysis were calculated, consistence of subgrade strength was done by carrying our liquid and plastic limits of different soil samples and finally design of the pavement was carried out by use of CBR design charts as recommended by AAHSTO.This report is organized in chapters with chapter one as Introduction, two Literature review, three Methodology, four results and analysis, five Conclusion and Recommendations.